Positive Sequence Current Phase-Based Improved Reverse-Power Protection and a PV Hosting Capacity Assessment Method for Spot Networks - Zhihua Zhang; Kun Wang; Qianpeng Zhao; Yongtao Tian; Lianghuan Li (IEEE Access, 2020)
A spot network is a special low-voltage distribution network with multiple sources supplying it in parallel. It can significantly enhance supply reliability and is beneficial for integrating a distributed energy resource (DER). However, because traditional reverse power protection in spot networks cannot identify the reverse power cause, DERs, especially photovoltaic (PV) hosting capacity, are limited. Meanwhile, no uniform method exists for assessing the PV injection capacity in spot networks. Based on comparing the positive sequence current phase, this article presents an improved reverse power protection and PV hosting capacity assessment method for spot networks. Current variation is adopted to identify the reverse power cause, and a spot network equivalent model with PV is built. The positive sequence current phase relationship at the reverse power protection location is analysed when different types of short circuit faults occur. A short circuit fault section can be determined by comparing the positive sequence current phase. The influence of the PV output current on the improved reverse power protection performance is analysed. Then, a PV hosting capacity assessment method with improved reverse power is presented based on the PV influence on protection instead of on node voltage. A simulation model based on an actual project is constructed using PSCAD software. The simulation results show that the improved reverse power protection significantly enhances the ability to inject PV into the spot network and operates correctly under faults. The theoretical PV hosting capacity agrees with the simulation results.